2017
DOI: 10.1002/j.1681-4835.2017.tb00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies and Sustainable Livestock Systems in Rural Communities

Abstract: The 43 rd Committee on World Food Security (CFS) convention reiterated the importance of livestock towards eliminating food insecurity across the globe. Livestock provides extensive services and products which are critical in addressing the issues of hunger, malnutrition, health and diseases. However, despite such importance, livestock systems across the globe continue to face the challenge of sustainability. In this research article, using ethnographic research techniques, we examine the Beitbridge livestock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…According to Aker (), one of the advantages of mobile telephony is that instead of being passive recipients of information through television, radio, and newspapers, farmers have the privilege of interaction and access to multiple sources of agribusiness information. Other studies like Kameswari, Kishore, and Gupta (), Aker and Ksoll (), Issahaku, Abu, and Nkegbe (), Onitsuka, Hidayat, and Huang (), Labonne and Chase (), Gwaka (), Abraham (), Gwaka (), and Mittal and Tripathi () have demonstrated a positive relationship between mobile telephony and agricultural development in various areas. The results from these studies emphasized that the introduction of mobile‐enabled agriculture information services have a higher impact in regions, which are poor and are remote from markets.…”
Section: Background and Theoretical Underpinningsmentioning
confidence: 90%
“…According to Aker (), one of the advantages of mobile telephony is that instead of being passive recipients of information through television, radio, and newspapers, farmers have the privilege of interaction and access to multiple sources of agribusiness information. Other studies like Kameswari, Kishore, and Gupta (), Aker and Ksoll (), Issahaku, Abu, and Nkegbe (), Onitsuka, Hidayat, and Huang (), Labonne and Chase (), Gwaka (), Abraham (), Gwaka (), and Mittal and Tripathi () have demonstrated a positive relationship between mobile telephony and agricultural development in various areas. The results from these studies emphasized that the introduction of mobile‐enabled agriculture information services have a higher impact in regions, which are poor and are remote from markets.…”
Section: Background and Theoretical Underpinningsmentioning
confidence: 90%
“…Also, the researcher connected to some of the research participants using the social technologies (Facebook and WhatsApp), and this has enabled the researcher to walk with (virtually) the research participants and engage in conversations with the research participants in a more relaxed way. Furthermore, the researcher continues to participate in the community practices, for instance, attending livestock auction (Gwaka, ), attending local entertainment shows, and eating at the local eating places. By doing so, the researcher continues to interact with the research participants as a participant‐researcher (Murthy, ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite most rural communities in developing countries lacking access to internet or mobile connection (Rey‐Moreno, Blignaut, Tucker, & May, ), Foster, Graham, Mann, Waema, and Friederici () suggest that there has been a massive improvement in the Internet access in developing countries. Relating to the study area, Gwaka () observed that most youths in the study area have knowledge of, have access to, and can use social media applications/services such as Facebook, WhatsApp, and Instagram. The use of DTs such as social technologies can serve a critical function of mobility—which is giving access.…”
Section: Youth Mobility In Rural Areasmentioning
confidence: 99%
See 2 more Smart Citations